Pesquisa de marcadores de indiferenciação celular em endométrio eutópico e ectópico de mulheres com e sem endometriose - Flavia Ribeiro de Oliveira (2011)
Endometriosis is a benign disease characterized by the presence of tissue resembling the endometrium outside uterine cavity. This disease has a high degree of morbidity associated with infertility and chronic pelvic pain. It is possible that the cause of endometriosis is polygenic and multifactorial, but the exact pathogenic mechanisms are still not entirely clear. In recent years, adult stem cells have been identified in several human tissues, including endometrium. These cells are probably involved in regenerative ability of endometrium cycle, and also in the pathogenesis of proliferative gynaecological diseases, such as endometriosis. The identification of stem cells in tissues is very complex, but these cells are supposed to be found through several assays such as clonogenicity, label retaining cells, side population cells, identification of undifferentiation markers and cellular differentiation. This study evaluated the expression of undifferentiation markers Musashi-1, Oct-4 e c-kit in eutopic endometrium of patients with and without endometriosis and endometriotic lesions. Samples were evaluated by immunohistochemistry through biotin-free polymer system. For statistical analysis, the chi square test was used for categorical variables and Kruskal-Wallis test was used for immunoreactivity scales. The material to be analysed comprised four samples of healthy endometrium and six samples of both ectopic and eutopic endometrium from patients with endometriosis. Musashi-1 presented a cytoplasmic and nuclear immunostaining pattern, while Oct-4 presented a predominantly nuclear pattern and c-kit a cytoplasmic and transmembranous pattern. The three markers were expressed in all endometrial compartments analysed (glandular, stromal and endothelial). A higher expression of Musashi-1 was noted in endothelium of patients with endometriosis (p<0,05). In some slides, Mushashi-1 and c-kit presented a cellular group pattern, which may correspond to stem cell niches. All markers showed a relatively high percentage and staining intensity. c-kit had a stromal expression comparatively higher than glandular expression, (p<0,05) and a higher immunoreacivity in stroma of eutopic endometrium of patients with endometriosis. In summary, it is possible that endometrial putative stem/progenitor cells have a role in pathogenesis of endometriosis, not only in the origin of ectopic implants but also in the process of neoangiogenesis